Knowledge and utilisation of preconception care and associated factors among women in Ethiopia: systematic review and meta-analysis - Alemu Degu Ayele; Habtamu Gebrehana Belay; Bekalu Getnet Kassa; Mulugeta Dile Worke (BMC, 2021)
Abstract Background Preconception care is the provision of biomedical, behavioural, and social health interventions provided to women and couples before conception. However, in Ethiopia, little is known and practised to support preconception care. Therefore, this study aimed to assess women's knowledge and utilisation of preconception care and its associated factors in Ethiopia using systematic review and meta-analysis. Method In the current meta-analysis, variables were searched from different electronic database systems, which included PubMed, Google Scholar, EMBASE, HINAR, Scopus, Web of Sciences, and Grey literature. Data were extracted using a standardised data collection measurement tool. The data were analysed by using STATA 14 statistical software. I2 tests assessed heterogeneity between the studies. A random-effect model was used to forecast the pooled knowledge and utilisation of preconception care. Results Thirteen full-text studies were included. The pooled prevalence of knowledge and utilisation of preconception care among women in Ethiopia was 30.95% and 16.27% respectivelly. Secondary education (OR = 2.78, 95% CI,2.01-3.85), college and above (OR = 5.05, 95% CI,2.70-9.44), and antenatal care (OR = 3.89, 95% CI, 1.69-8.98) were significantly associated with knowledge level whereas; age (OR = 2.43, 95% CI, 1.30-4.53) and knowledge on preconception care (OR = 3.95, 95% CI,2.35-6.62) were positively associated with utilisation of preconception. Conclusions Women's level of knowledge and utilisation of preconception care was significantly low. Educational status and antenatal care follow-up were factors shown to affect knowledge of preconception care. Age and having a sound knowledge of preconception care indicated a significant association towards utilisation of preconception care. Thus, integrating preconception care strategies and policies that can address all the components of preconception care services with other maternal and child health services will be essential when designing effective implementation strategies to improve preconception care uptake. Besides this, advocating for better education for women, awareness creation, and increasing antenatal care services are essential. Prospero registration: CRD42020218062